2014
DOI: 10.5897/jvmah13.0211
|View full text |Cite
|
Sign up to set email alerts
|

Pre-weaning kid mortality in Adamitulu Jedokombolcha District, Mid Rift Valley, Ethiopia

Abstract: A longitudinal study was conducted, from October 2008 to April 2009, on 188 kids born from flocks of 50 randomly selected households in Aneno and Edokontola villages in Adamitulu Jedokombolcha district, mid rift valley, Ethiopia. The aim of the study was to estimate pre-weaning mortality, identify associated factors and establish possible causes of death in goat kids. Data collected were used to evaluate the effect of sex, birth weight, parity, type of birth and some management practices on preweaning mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Kids in their rst 45 days of life were at greater risk of being killed by exposure to extreme cold conditions in the area. This observation agrees with previous results by Alula et al (2014) who reported that climate-related problems always pose a greater risk to young stock kept under rural farming conditions. An improved housing infrastructure is necessity for better survival of young kids in resource-constrained communities.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Kids in their rst 45 days of life were at greater risk of being killed by exposure to extreme cold conditions in the area. This observation agrees with previous results by Alula et al (2014) who reported that climate-related problems always pose a greater risk to young stock kept under rural farming conditions. An improved housing infrastructure is necessity for better survival of young kids in resource-constrained communities.…”
Section: Discussionsupporting
confidence: 93%
“…Pneumonia occurs when infectious and non-infectious agents cause the lungs of goats to become in amed (Bhattarai, 2021;Vandana et al, 2015). The most frequent causes of respiratory infection and death are Pasteurella multocida or Mannheimia haemolytica (previously called Pasteurella haemolytica) (Alula et al, 2014;Diriba & Kebede, 2020). Heath complications from these pathogens are associated with poor management practices, such as overcrowded pens, poor housing conditions and other stressful conditions increasing susceptibility of the kids to P. multocida and M. haemolytica pneumonias (Arsoy, 2020;Yasmin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, by efforts of Government, NGOs and Development Projects, Red Maradi goats are widely distributed in Niger and West African countries. The major constraint limiting the productivity of Red Maradi goat is the nutritional management of dams with repercussion on milk production, live weight losses, low post-natal performances of kids (Pamo et al, 2007;Snyman, 2010;Ukanwoko et al, 2012;Petros et al, 2014), and slow growth rate of kids (Nnadi et al, 2007). Djibrillou et al (1998) reported a general body weight loss of red Maradi goats fed untreated or urea treated straws supplemented with or without concentrate and attributed this to a negative energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia occurs when infectious and non-infectious agents cause the lungs of goats to become inflamed (Bhattarai, 2021;Vandana et al, 2015). The most frequent causes of respiratory infection and death are Pasteurella multocida or Mannheimia haemolytica (previously called Pasteurella haemolytica) (Alula et al, 2014;Diriba & Kebede, 2020). Heath complications from these pathogens are associated with poor management practices, such as overcrowded pens, poor housing conditions and other stressful conditions increasing susceptibility of the kids to P. multocida and M. haemolytica pneumonias (Arsoy, 2020;Yasmin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%